2011
DOI: 10.1152/ajprenal.00282.2010
|View full text |Cite
|
Sign up to set email alerts
|

The rat kidney contains high levels of prouroguanylin (the uroguanylin precursor) but does not express GC-C (the enteric uroguanylin receptor)

Abstract: The peptide uroguanylin (Ugn) regulates enteric and renal electrolyte transport. Previous studies have shown that Ugn and its receptor GC-C (a ligand-activated guanylate cyclase) are abundant in the intestine. Less is known about Ugn and GC-C expression in the kidney. Here, we identify a 9.4-kDa polypeptide in rat kidney extracts that appears, based on its biochemical and immunological properties, to be authentic prouroguanylin (proUgn). This propeptide is relatively plentiful in the kidney (~16% of intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 92 publications
3
20
0
Order By: Relevance
“…Further, eliminating uroguanylin, but not GUCY2C, expression produces hypertension in mice (40). Moreover, while the evidence base has been ambiguous, recent studies have confirmed the absence of GUCY2C expression in kidney in placental mammals (41). Taken together, these observations demonstrate that renal effects of these peptides are mediated by paracrine signaling that is independent of GUCY2C and cGMP.…”
Section: Discussionmentioning
confidence: 92%
“…Further, eliminating uroguanylin, but not GUCY2C, expression produces hypertension in mice (40). Moreover, while the evidence base has been ambiguous, recent studies have confirmed the absence of GUCY2C expression in kidney in placental mammals (41). Taken together, these observations demonstrate that renal effects of these peptides are mediated by paracrine signaling that is independent of GUCY2C and cGMP.…”
Section: Discussionmentioning
confidence: 92%
“…The activation of this receptor promotes an increase of cGMP intracellular content, which activates PKG. Although several studies demonstrated that the guanylin classic receptor GC-C is expressed in rat renal cortex (10,18), a recent study suggested otherwise (45). As seen in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Accumulating data have provided evidence that guanylin peptides are produced in the kidney (likely in response to hypernatremia) and have paracrine/autocrine functions in the cells along the nephron [5, 48, 49]. GN and UGN mRNAs are expressed in rodent and human kidney epithelial cells [3, 12, 15, 32, 5052].…”
Section: The Guanylin Peptidesmentioning
confidence: 99%
“…Moreover, high extracellular [NaCl] influences UGN expression in cultured kidney cells [52, 53, 55, 56]. Qian et al [49] in a recent, thorough experimental study in rats, demonstrated high proUGN abundance locally synthesized in renal distal tubule segments. The authors provided evidence for an intrarenal UGN system that differs from the intestinal system in its regulatory mechanisms and in the receptor targeted by the peptide, which is not the enteric UGN receptor, GC-C.…”
Section: The Guanylin Peptidesmentioning
confidence: 99%
See 1 more Smart Citation